Resiliensi Ibu Berkarir dalam Mendampingi Kegiatan Belajar Online pada Era Pandemi - Heleni FIltri; Siti Fadillah; Sean Marta Efastri (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2023)
The Covid-19 pandemic that has occurred since the end of 2019 has caused many changes to occur in various aspects of life in the world and in Indonesia in particular. One of them is the educational aspect where learning that was originally carried out face-to-face at school is now being carried out online. This study aims to describe the resilience of working mothers in the Covid-19 Pandemic Era in assisting early childhood online learning activities. This type of research uses a quantitative descriptive method. The population in this study were working mothers (parents) whose children attended early childhood education in the Rumbai sub-district. Based on the resilience score of the research sample, it is in the low category. This shows that accompanying school children from home has low resilience. A low level of resilience will have an impact on a high level of stress. This shows the importance of accompanying children when learning from home to educate parents who have low levels of resilience. One effort that can be done by the teacher is with home visits, so that students can be accompanied by the teacher even though there is not much time. Parents said that the learning process would be more effective if it was done face to face. However, parents also feel worried if their children are exposed to Covid-19. Parents said that online learning without material would make children ask parents. The pandemic condition that requires the learning process to be carried out using online methods is one of the stressors for many people, including parents.